2016
DOI: 10.1016/j.apsb.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

An update on the role of intestinal cytochrome P450 enzymes in drug disposition

Abstract: Oral administration is the most commonly used route for drug treatment. Intestinal cytochrome P450 (CYP)-mediated metabolism can eliminate a large proportion of some orally administered drugs before they reach systemic circulation, while leaving the passage of other drugs unimpeded. A better understanding of the ability of intestinal P450 enzymes to metabolize various clinical drugs in both humans and preclinical animal species, including the identification of the CYP enzymes expressed, their regulation, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 100 publications
(141 reference statements)
5
76
0
Order By: Relevance
“…We demonstrated that testosterone metabolism mostly occurred in the ileum. This result is in line with a previous study showing that protein levels of CYP3A, which exhibits testosterone 6b-hydroxylase activity (Emoto et al, 2000b), is highest in the proximal region of the intestine and declines in the distal part (McKinnon et al, 1995;Paine et al, 1997;Xie et al, 2016;Drozdzik et al, 2018). In addition, other studies revealed that CYP3A and CYP2C are the major intestinal CYPs, accounting for approximately 80% and 18%, respectively, of all CYPs (Thelen and Dressman, 2009;Nakamura et al, 2016).…”
Section: Downloaded Fromsupporting
confidence: 90%
“…We demonstrated that testosterone metabolism mostly occurred in the ileum. This result is in line with a previous study showing that protein levels of CYP3A, which exhibits testosterone 6b-hydroxylase activity (Emoto et al, 2000b), is highest in the proximal region of the intestine and declines in the distal part (McKinnon et al, 1995;Paine et al, 1997;Xie et al, 2016;Drozdzik et al, 2018). In addition, other studies revealed that CYP3A and CYP2C are the major intestinal CYPs, accounting for approximately 80% and 18%, respectively, of all CYPs (Thelen and Dressman, 2009;Nakamura et al, 2016).…”
Section: Downloaded Fromsupporting
confidence: 90%
“…Although the exact mechanism of the low F of buspirone in rats and humans remains unclear, buspirone administered orally is believed to undergo extensive first-pass metabolism in humans (Kim et al, 2016). In particular, previous studies have reported the markedly high E G of buspirone in humans, which was calculated to be 0.89 according to the grape fruit juice (GFJ) method (Gertz, Davis, Harrison, Houston, & Galetin, 2008) and 0.78 according to the drug-drug interaction (DDI) method (Hisaka, Nakamura, Tsukihashi, Koh, & Suzuki, 2014;Xie, Ding, & Zhang, 2016). If this holds true for the rat pharmacokinetics of buspirone, it is plausible that the higher expression and activity of intestinal CYP3As observed in 1,25(OH) 2 D 3 -treated rats than in control rats (Figures 1 and 2) could lead to an increase in the E G of buspirone, and consequently the systemic exposure (AUC and F) of buspirone could be reduced by 1,25(OH) 2 D 3 treatment (Table 4).…”
mentioning
confidence: 99%
“…The human small intestine expresses multiple CYPs and metabolizes various clinical drugs (Paine et al, 2006;Xie et al, 2016). The metabolic activities of CYP2C9, CYP2C19, CYP2D6, CYP3A4/5, and UGT, which are expressed in the human small intestine, were markedly increased by using 8-Br-cAMP and IBMX (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Human iPS cell-derived intestinal stem cells were treated with 1 mM 8-Br-cAMP or 500 µM IBMX at day 8-13 or day 13-26 during the intestinal differentiation. After terminal differentiation, the expression levels of intestinal specific markers, such as villin 1 (Boller et al, 1988;Landry et al, 1994), fatty acid-binding protein 2 (FABP2) (Gajda et al, 2015), dipeptidyl peptidase-4 (DPP4) (Darmoul et al, 1994), and pharmacokinetics-related genes such as CYP3A4 (Paine et al, 2006;Xie et al, 2016), SLC15A1/PEPT1, and ABCB1/multidrug resistance 1 (MDR1) (Hilgendorf et al, 2007;Yoshida et al, 2013), were markedly increased in the cells treated with 8-Br-cAMP and IBMX compared with cells differentiated without these compounds (control group) ( Fig. 1).…”
Section: Effect Of Camp Signaling On Differentiation From Human Ips Cmentioning
confidence: 99%
See 1 more Smart Citation